Technical and environmental impacts of coal waste used as a soil stabilizer in construction projects of forest roads - Mansouri, Sara (Array, 2021)
Many pozzolans are waste products from industrial processes. Every year a huge amount of coal waste is gathered from the coal washing plant in the Hyrcanian forests of Iran. These materials can be used for soil stabilization in construction and maintenance projects of forest roads. This paper aims to (a) investigate the role of coal waste (CW) as a soil stabilizer and (b) determine the changes in soil specification regarding the environmental pollution in different combinations of materials (soil, lime (4 and 6%) and CW (3, 6, 9 and 12%)). For this purpose, different technical and environmental analysis and laboratory tests were performed. Technical tests showed that the soil liquid limit and maximum dry density decreased with an increase in lime and CW contents. Addition of CW could increase the soil CBR, UCS and OMC. According to XRD test, the addition of CW and lime can increase the size of crystals in stabilized soil samples. Environmental analysis showed that the use of stabilizer significantly reduced the concentration of heavy metals such as Cd, Cr and Pb. Also, all of the metal concentrations leached from samples satisfied the required criteria, but the addition of lime and CW increased the concentration of N, P, and K. These changes can increase the invasive species consistent with calcareous soil conditions along the roads. According to the results, the combination of coal waste and lime can be one of the best methods for in situ remediation. It would, however, be better to use a minimum amount of stabilizer in pavement layers of access roads due to environmental sensitivity.